DETERMINAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Kasus Kementerian Perindustrian Republik Indonesia Unit Satuan Kerja di Provinsi Lampung) - Meiliana, Reva; Mustika, Dian; Saputra, Rizki (Universitas Teknokrat Indonesia, 2023)
This study aims to empirically prove about the effect of regulatory compliance, budget goals clarity, and accounting control system on the performance accountability of government agencies. The sample in this study are functional officials involved in managing the accountability of government performance agencies in the Administrative Section of the Ministry of Industry of the Republic of Indonesia Work Unit in Lampung Province. The sampling technique in this study was purposive sampling. The analytical method used in this study is multiple linear regression using the SPSS Version 25 analysis tool. The results of this study indicate that regulatory compliance, budget goals clarity, and accounting control system had an effect on performance accountability of government agencies in the Ministry of Industry Republic of Indonesia Work Unit in Lampung Province.